Serial Exercise Testing and Echocardiography Findings of Patients With Kawasaki Disease - Lin, Ko-Long; Liou, I-Hsiu; Chen, Guan-Bo; Sun, Shu-Fen; Weng, Ken-Pen; Li, Chien-Hui; Tuan, Sheng-Hui (Frontiers in Pediatrics, 2022)
Objective: Kawasaki disease (KD) is the most common form of pediatric vasculitis. We evaluated the influence of KD on cardiopulmonary function and analyzed the echocardiographic findings of patients with KD through serial follow-ups from childhood to adolescence. Methods: This was a retrospective study. We recruited patients with KD after the acute stage who underwent at least two (with >1 year interval between visits) cardiopulmonary exercise testing (CPET) and echocardiographic examinations in the last 10 years. Cardiopulmonary function was determined through CPET on a treadmill. The maximum Z-score (Max-Z) of the proximal left anterior descending coronary artery or right coronary artery was determined using echocardiography. Healthy peers matched for age, sex, and body mass index with serial CPET and echocardiographic data were recruited as a control group. Results: Each group consisted of 30 participants with comparable basic characteristics. No significant differences in the variables of the first CPET were observed between the two groups. In the final CPET, the control group had a higher percentage of measured oxygen consumption (VO2) at the anaerobic threshold (AT) to the predicted peak VO2 (p = 0.016), higher percentage of measured peak VO2 to the predicted peak VO2 (p = 0.0004), and higher VO2 at AT (p < 0.0001) than those of the KD group. No significant difference in the percentage of distribution of Max-Z was observed between the first and final echocardiographic examinations. Conclusions: Children with a history of KD had comparable exercise capacity to their healthy peers. However, in the follow-up, the aerobic metabolism and peak exercise load capacities of adolescents with KD were significantly lower than those of control adolescents.